KEEFEKTIFAN MODEL PEMBELAJARAN LANGSUNG BERBANTU MEDIA GAMBAR UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS I SD NEGERI 016 MARSAWA - Timoria Timoria (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
Social studies learning about social community that is useful for future student life. To achieve these objectives, the teacher must work hard in striving, creating a learning process that makes it easy for students to explore the information provided. This research was carried out in class I 016 Marsawa Public Elementary School with a total of 22 students out of 15 men and 7 women. The design of this study uses classroom action research which consists of two cycles by applying a direct learning model assisted by media images. The results of the study prove, on the base score, students who complete as many as 10 (45.4%) while students who did not complete as many as 12 (54.5%) people with an average grade on the base score of 51.8 with the category of incomplete. Cycle I, as many as 16 students (72.7%), while students who did not complete as many as 6 (27.3%) people with an average grade of 73.4. The increase in class average from the base score to the first cycle was 21.6 with a complete category. Cycle II, students who completed as many as 20 (90.9%) while students who did not complete as many as 2 (9.1%) people with an average grade of 88.7. Increased class average from the base score to the second cycle of 21.6 with the category of completion. It can be concluded that by applying the direct learning model assisted by effective image media to improve social studies learning outcomes of Grade I students of SD Negeri 016 Marsawa